2012
DOI: 10.1016/j.mhpa.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the relationship between physical activity and smoking among psychiatrically hospitalized adolescents

Abstract: Physical activity has been identified as a protective factor with regard to tobacco use, such that physically active adolescents are less likely to initiate smoking, and smokers are less physically active than non-smokers. These findings, along with the well-documented benefits of exercise on mood and well-being in adults, have stimulated interest in exercise-based smoking cessation interventions. However, little research has explored the relationship between physical activity and smoking characteristics withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Several factors such as the duration and intensity of exercise sessions, duration of smoking abstinence before interventions, socio-demographic factors (e.g. age, gender), smoking history (cigarette dependence, number of cigarettes per day), general fitness level of the sample (low, moderate or high) and general well-being and motivation of the sample, may influence the strength of the relationship between exercise and craving or withdrawal symptoms (Haasova et al 2016 , 2014 ; Bloom et al 2012 ; Tritter et al 2015 ). Some studies showed that short bouts of exercise with higher intensity have greater effects on craving and withdrawal symptoms than lower-intensity exercise units (Daniel et al 2004 ; Kurti and Dallery 2014 ; Janse van Rensburg et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors such as the duration and intensity of exercise sessions, duration of smoking abstinence before interventions, socio-demographic factors (e.g. age, gender), smoking history (cigarette dependence, number of cigarettes per day), general fitness level of the sample (low, moderate or high) and general well-being and motivation of the sample, may influence the strength of the relationship between exercise and craving or withdrawal symptoms (Haasova et al 2016 , 2014 ; Bloom et al 2012 ; Tritter et al 2015 ). Some studies showed that short bouts of exercise with higher intensity have greater effects on craving and withdrawal symptoms than lower-intensity exercise units (Daniel et al 2004 ; Kurti and Dallery 2014 ; Janse van Rensburg et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Killen and Fortmann 1997 ; Piasecki et al 2003 ), brief bouts of physical activity (PA) have a strong acute effect on reducing cigarette cravings (Haasova et al 2013 ; 2014 ; Roberts et al 2012 ), and it may be that these effects accumulate across the day. For example, Bloom et al ( 2012 ) reported a negative association between cigarette withdrawal symptoms and weekly PA but only among male psychiatrically hospitalised adolescents, and not females (Bloom et al 2012 ). It is important to determine if habitual or chronic PA is associated with both acute and more enduring or stable cravings (Tiffany and Wray 2012 ) in the general population of smokers and to examine whether these associations vary according to different sub-groups.…”
Section: Introductionmentioning
confidence: 99%
“…moderate and vigorous exercise has greater acute effects than light intensity; Haasova et al 2014 ), socio-demographic factors (e.g. gender differences in motivation for smoking and PA; Bloom et al 2012 ), satisfaction from smoking and cigarette dependence. There are also a number of shared correlates of smoking and PA, with lower socio-economic groups more likely to smoke, drink alcohol and being less active (Bellis et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%